Ancient Jerusalem revealed - Gevaʿ, Hilel ca. 20./21. Jh. (Israel Exploration Society, 1994)
Ancient Jerusalem Revealed presents the archaeological discoveries in Jerusalem from the mid-1970s through the 1980s and into the 1990s. It continues and complements the first volume of Jerusalem Revealed. Together, both volumes broadly summarize the results and achievements of the recent archaeological activities in Jerusalem, and testify to the tremendous efforts invested during the last two-and-a-half decades by Israeli scholars and archaeological institutions. They cover all of its historical periods-under Jewish, Christian and Muslim rule; times of achievement and prosperity, and eras of decline and neglect.